Agent-based Modeling of the Spatial Diffusion of Tourist Flow—A Case Study of Sichuan, China. Issue 1 (2nd January 2016) - Qiu, Rongxu; Xu, Wei; Li, Shan
ABSTRACT: This study presents an agent-based model that simulates the tourist flow diffusion process of a tourism destination system. The model begins by building simple tourist agents, whose main activities are selecting tourist spots and organizing tourism schedules given their unique financial and time constraints. Next, the model utilizes tourist spot manager agents, whose responsibilities are alerting tourists about crowdedness and/or posting advertisements to attract tourists. A regional tourist flow model was developed to simulate the decisions and behaviors of these agents and predict tourist flow direction and distribution. The model was applied to the Sichuan province in China, which has 41 Class 3A and above tourism spots. Under different decision-making scenarios, the results of the model simulations showed that northwest, northeast, southeast, and southwest are the four main tourist flow directions and that crowd-alert would assist in effectively regulating tourist flow and tourism distribution patterns except when long-distance tourists dominate.